Social Responsibility in the Area of Labour Practices in the Context of Employer Branding - Urszula Gołaszewska-Kaczan (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2023)
Theoretical background: In an environment of ever-increasing competition, companies are looking for proven ways to gain competitive advantage. This translates into an increased interest in goodwill and the factors that allow its value to be raised. Goodwill is the differentiating ability of a company, compared to others or an average company, to make a profit. One of the factors that can build goodwill is the company’s image as an employer. Therefore, it is very important for companies to undertake employer branding activities. Employer branding is company’s activities aimed at achieving a positive image and becoming the so-called employer of choice. Among these activities, the company’s implementation of the concept of corporate social responsibility has an important place. Certainly, a company’s activity in any CSR area translates into the way the company is perceived by employees, but activities in the area of employee practices are of primary importance. Enterprises can take a wide variety of measures in relation to employees, tailored to their specific characteristics, capabilities and competencies, as well as the needs reported by employees.